Mechanical Properties of Heat Treated Secondary AlSi12Cu1Fe Cast Alloy at Room Temperature - Lenka Hurtalova; Eva Tillova; Maria Chalupova (Communications - Scientific letters of the University of Zilina, 2012)
The contribution describes changes of mechanical properties (strength tensile, absorbed energy and Brinell hardness) in secondary (recycled) eutectic aluminium-silicon cast alloy – AlSi12Cu1Fe during solution treatment. This work presents the influences of the solution treatment by 525 °C, 545 °C and 565 °C with the holding time 2, 4, 8, 16 and 32 hours, water quenching at 40 °C and natural aging with holding time 24 hours. Mechanical properties were measured in line with STN EN ISO at room temperature. Solution treatment has led to changes in mechanical properties, caused by the changes in microstructure including the spheroidization and coarsening of eutectic silicon, gradual disintegration, shortening and thinning of intermetallic phases.